Comparative Study of Headed Stud Shear Connector and U- Shaped Shear Connector Through Numerical Modelling - Ghimire, Uspal (My University, 2022)
Shear connectors are one of the most important elements required for the composite construction. Composites structure usually fail at the shear between two structural elements i.e. steel and concrete. Hence, many researches has been carried out to enhance its properties so that the bond between two composites can be strengthened. In addition to increasing the strength of concrete, cost of shear connector also needs to be minimized hence stud connector has been modified into U-shaped connector. In this project, a 3-D FEM model of pushout test of Headed stud and U-shaped shear connector has been simulated in ABAQUS and analysis has been carried out under gradual loading. The obtained result of headed stud is compared with the experimental value. The same material properties of headed stud is allotted to U-shaped connector and the analysis was carried out. The output of both connectors were contrasted. It was found that the load bearing capacity of U-shape connector is 20% more than that of headed stud shear connector. The load-slip behaviour of headed stud and U-shape connector are found to be similar. The stress pattern at different location on U-shape connector follows a symmetric pattern from mid-point where as in case of headed stud it is maximum at roots and decreases while moving towards the other end. From the economic point of view U-shape connector can be more economical than that of headed stud connector as former can provide more bearing capacity as compared to the latter one on same mass. From the optimisation of U-shape connector it can noted that 36 percent less volume of steel is required than that of headed-stud connector for the same peak load bearing capacity.
Keywords: Headed Studs; Shear Connectors; Numerical Modelling; ABAQUS; Composites